2014
DOI: 10.1101/006783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hybrid origins and the earliest stages of diploidization in the highly successful recent polyploidCapsella bursa-pastoris

Abstract: Whole-genome duplication (WGD) events have occurred repeatedly during flowering plant evolution, and there is growing evidence for predictable patterns of gene retention and loss following polyploidization. Despite these important insights, the rate and processes governing the earliest stages of diploidization remain poorly understood, and the relative importance of genetic drift, positive selection, and relaxed purifying selection in the process of gene degeneration and loss is unclear. Here, we conduct whole… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
98
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(112 citation statements)
references
References 64 publications
11
98
3
Order By: Relevance
“…Indeed, the recent colonization history of A. lyrata especially in northern Europe has likely been associated with strong population bottlenecks or effective population size reduction (Mattila, Tyrmi, Pyhäjärvi, & Savolainen, 2017;Pyhäjärvi, Aalto, & Savolainen, 2012;Ross-Ibarra et al, 2008;Savolainen & Kuittinen, 2011), which is in contrast to the large and relatively stable population of C. grandiflora (Douglas et al, 2015;Slotte, Foxe, Hazzouri, & Wright, 2010;Slotte et al, 2013;St. We chose these species because they have similar mating systems (both are self-incompatible outcrossers) and genome structure, and because previous research suggests considerable differences in the demographic histories of some populations.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the recent colonization history of A. lyrata especially in northern Europe has likely been associated with strong population bottlenecks or effective population size reduction (Mattila, Tyrmi, Pyhäjärvi, & Savolainen, 2017;Pyhäjärvi, Aalto, & Savolainen, 2012;Ross-Ibarra et al, 2008;Savolainen & Kuittinen, 2011), which is in contrast to the large and relatively stable population of C. grandiflora (Douglas et al, 2015;Slotte, Foxe, Hazzouri, & Wright, 2010;Slotte et al, 2013;St. We chose these species because they have similar mating systems (both are self-incompatible outcrossers) and genome structure, and because previous research suggests considerable differences in the demographic histories of some populations.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, hybridization has long been recognized to play an important role in plant evolution, with many reported cases of related species that, either punctually or continuously in their life history, have experienced gene flow, leading to introgression of adaptive traits or hybrid speciation (2)(3)(4)(5)(6)(7)(8)(9). Thus, the "tree of life" is considered more as a complex network than an actual tree (10,11).…”
mentioning
confidence: 99%
“…For instance, it is estimated that ;16% of the genes for Arabidopsis are still present in duplicate following the most recent WGD that occurred ;49 million years ago (mya; Vanneste et al, 2014a), while 75% of the genes are still present in duplicate in soybean (Glycine max), which underwent a WGD ;13 mya (Schmutz et al, 2010). Whether these genes will be retained indefinitely is still an unresolved question (Buggs et al, 2012;McGrath and Lynch, 2012;Douglas et al, 2015), although the lower numbers of retained genes reported for more ancient WGD events seems to suggest that, at least for a subset of genes, dosage constraints eventually get relaxed, leading to functional diversification or loss of these genes.…”
Section: Introductionmentioning
confidence: 99%